Exploring agency with and in participatory research on artificial intelligence in everyday information practices - Aira Huttunen; Tuula Nygård; Noora Hirvonen (Information Research: An International Electronic Journal)
Introduction. Artificial intelligence (AI) tools are increasingly integral to the everyday information practices of young people in digitalised societies. These tools are suggested to shape human agency; that is, human capacity to act in meaningful ways.